Analyzing and comparing augmented reality and virtual reality assisted vocabulary learning: a systematic review - Mike Minwen Zhang; Harwati Hashim; Melor Md Yunus (Frontiers in Virtual Reality)
IntroductionThe integration of augmented reality (AR) and virtual reality (VR) into language learning, particularly vocabulary learning, has been spotlit by a growing body of research in recent years. However, there is a notable lack of comprehensive reviews analyzing the latest research on AR-assisted vocabulary learning (ARVL) and VR-assisted vocabulary learning (VRVL), especially the ones systematically comparing the vocabulary learning (VL) processes as well as outcomes, including the effectiveness of vocabulary gain and retention within the AR/VR learning environments.MethodsTo fill this research gap, a total of 37 empirical studies from the last five years (2020-2024) were meticulously selected from the domains of ARVL and VRVL and then analyzed and compared across five dimensions: main characteristics, VL process, VL effectiveness, their main benefits and limitations.ResultsKey findings reveal that while VRVL studies employed head-mounted displays (HMD) more frequently, ARVL studies greatly outnumbered their VRVL counterparts, with a predominant academic interest in non-wearable AR. Higher education was the main focus of the research, with elementary education coming in second. Although most VRVL studies took a more thorough approach, ARVL research mostly concentrated on basic vocabulary knowledge. By incorporating auditory effects, a sizable portion of VRVL studies improved the multimedia VL experience. The intentional learning approach was preferred over the incidental approach in both fields, while incidental learning was slightly more common in VRVL studies. Most studies on ARVL and VRVL indicate that learners in AR/VR-supported environments achieved significantly greater vocabulary gains than those using traditional methods. Additionally, the dual measurements of vocabulary gain and retention in VRVL studies have been examined more rigorously, and the impact of VRVL has been found to be potentially more effective than that of ARVL.SuggestionsIt is suggested that wearable devices in ARVL studies, VRVL in elementary and preschool settings, and ARVL for junior high learners, vocabulary retention in ARVL and VRVL contexts demand further investigation. It is advisable to conduct comparative empirical studies and meta-analyses regarding the effectiveness of VL in these two learning modes. Future research could benefit from integrating ARVL and VRVL to create a synergistic approach that further supports vocabulary learning.